Improvement in seed germination in Ghingaru (Pyracantha crenulata (D. Don) M. Roemer) at low temperature through pre-treatments - Patade, Vikas Yadav; Singh, Nirbhay; Grover, Atul; ,, Madhubala (Indian Forester, 2020)
Ghingaru (Pyracantha crenulata (D. Don) M. Roemer) is an important Himalayan medicinal shrub belongs to family Rosaceae. Fruits of the plant are rich in antioxidants, crude protein, crude fiber and carbohydrates. The fruit extract is reported to have antimicrobial activity and cardio-tonic beverage is prepared from it. However, a very little scientific information is available on its mass propagation through seed germination. Further, poor germination of seeds under the prevailing low temperatures in the Himalayan hills affects nursery production for its mass propagation. Here we report improvement in seed germination through chemical pretreatments with potassium nitrate and polyethylene glycol 8000 (PEG) at low temperature of 150C. Before sowing seed pre-treatments with potassium nitrate (500 mM) and PEG (12.5 mM) significantly (P â‰¤ 0.05) enhanced seed germination (by 36 and 54% respectively) as well as its rate (by 65 and 58% respectively) than the control. The seedlings obtained from the pre-treated seeds grew vigorously after transplanting under the field conditions. The standardized seed pre-treatments will enable an early and rapid establishment of nursery seedlings for propagation of the economically important plant at the Himalayan regions.